Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1002/asia.201901715
|View full text |Cite
|
Sign up to set email alerts
|

Self‐assembly of a Sequence‐shuffled Short Peptide Amphiphile Triggered by Metal Ions into Terraced Nanodome‐like Structures

Abstract: We highlight the structural diversity of strategically designed two short peptide amphiphiles (sPAs) and describe their structure–function relationship studies. The shuffling of two key amino acids, that is, tyrosine and phenylalanine, in a designed sPA lead to a pair of constitutional isomers. Such small and strategic alteration can bring a substantial change in the self‐assembling pattern. Inspired from the naturally occurring metallopeptides, bioactive transition‐metal ions were used for constructing the un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
70
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 29 publications
(76 citation statements)
references
References 63 publications
0
70
0
Order By: Relevance
“…(AgNPs) over diatom surface for making high efficiency dye synthesized solar cell (DSSC) and hence can be used as potential devices forrenewable & sustainable energy sources . The presence of non‐covalent forces facilitate the self assembling phenomenon of multifunctional short peptide conjugates and amino acids over diatom and other biological cell surfaces . Ultra short peptide and amino acid‐based organic biomaterial potentially interacts with membrane proteins and hence quickly respond towards the biological cells which make them favorable biomaterial for surface modification or biofabrication for numerous biological applications …”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…(AgNPs) over diatom surface for making high efficiency dye synthesized solar cell (DSSC) and hence can be used as potential devices forrenewable & sustainable energy sources . The presence of non‐covalent forces facilitate the self assembling phenomenon of multifunctional short peptide conjugates and amino acids over diatom and other biological cell surfaces . Ultra short peptide and amino acid‐based organic biomaterial potentially interacts with membrane proteins and hence quickly respond towards the biological cells which make them favorable biomaterial for surface modification or biofabrication for numerous biological applications …”
Section: Figurementioning
confidence: 99%
“…AFM observation revealed that tyrosine self assembled into fibrous structures of submicron length (Figure A−D). It is based on our previous reports, the presence of bioactive transition metal ions have the ability to transform the self assembled structure of ultrashort peptides conjugates and hence can have the applications in biotechnology . Tyrosine is highly equipped with various physicochemical properties and therefore it is easy to investigateany considerable changes which occur due to the presence of external stimuli, such as metal ions, using spectroscopic and microscopy techniques.…”
Section: Figurementioning
confidence: 99%
“…It is otherwise stated that an atomic level modification nearby to N‐and C‐terminal Phe moiety of tripeptide Phe−Phe−Phe(N→C) by −OH group leads a pair of constitutional isomers (Scheme , bottom). Such rational design of these isomeric tripeptides was an inspiration from our previously reported work where we have shown that constitutional isomers of short peptides amphiphiles followed different paths of self‐assembly pattern . Whilst several factors are known to affect the self‐assembly process followed by nanostructures of peptide conjugates, we found that shuffling of the position of functional group(s) or amino acid moieties, is poorly explored in the literature .…”
Section: Introductionmentioning
confidence: 97%
“…Aromatic peptide, peptide amphiphiles, hairpin peptides to name a few, have frequently been used from the past decades. However, self‐assembly of designed short peptides conjugates also provides an excellent source of inspiration for engineering fascinating nanostructure of unusual shape and size …”
Section: Introductionmentioning
confidence: 99%
“…Lipid amphiphiles containing short peptides are also synthetic materials with many features that make them of interest to those working in the formation of fibrous and spherical nanostructures with metal nanoparticles and metal ions [25–28] . These unique nanostructures are able to form various assemblies based on intermolecular interactions due to their hydrophilic amino acids and hydrophobic alkyl chains.…”
Section: Introductionmentioning
confidence: 99%